THE IMPORTANCE OF PHYSICAL ACTIVITY AEROBICS AS A MEANS OF PREVENTION OF CARDIOVASCULAR DISEASE AND PROMOTION OF QUALITY OF LIFE IN YOUNG ADULTS (Fiep Bulletin - online, 2013)
Benefits of aerobic physical activity are associated with health and welfare, as well as to decrease the risk predisposing to the emergence and development of organ dysfunction related to inactivity, highlighting in this study, young adults enrolled in higher education. The extension project "Forum for Sports and Leisure in FAEFID / UFJF" in the form swimming, aims at promoting the leisure and health through the practice of university sports. It was used as an instrument of a questionnaire survey aiming to raise data on physical activity. The subjects were 30 students of various courses of UFJF. The activities developed with the participants were brought in line with the level of individual performance in the water, including the initiation and improvement of swimming as well as physical conditioning. These were held in the pool of FAEFID by 3 to 4 meetings per week for 4 months. The results of this study were statistically analyzed and showed that 40% of university students not practiced any physical activity. For 47% of the participants, the aim of the sport by the search was to obtain a good physical condition, to 23% this goal is related to learning or improving swimming, 17% showed interest in improving the quality of life and health, and to the remaining 13%, the goal is associated with other aspects. All participants showed improvement in quality of life and well-being physical and psychological noticed that physical activity for the group has not been a habit from day to day, which directly influences the present and future health of these individuals.
Keywords: quality of life; sedentary lifestyle and swimming